Jokowi After the First Term – Indonesia’s Counterterrorism Policy : An Appraisal - Anindya, Chaula Rininta (2019)
President Joko “Jokowi” Widodo’s re-election would allow policy continuity in combating terrorism. What is his legacy? What should be done to improve it?